1964
DOI: 10.1002/ar.1091490112
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium‐induced injury of the rat testis

Abstract: It is well known that cadmium chloride administered as single, subcutaneous, sub-toxic doses selectively damages the rat testis, producing irreversible injury of the germinal epithelium and temporary damage to the interstitial tissue. Studies reported here demonstrate that: (1) this injury represents an ischemic necrosis secondary to rapid production of intertubular edema ( 4 to 6 hours), increased intratesticular pressure, with or without associated hemorrhage, and ultimate interference with testicular blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0
1

Year Published

1964
1964
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 13 publications
5
41
0
1
Order By: Relevance
“…It is suggested that the cadmium ion affects either the testicular vessels and their epididymal branches (Gunn, Gould, & Anderson, 1963), or their end-arterial capillary bed (Mason, Brown, Young & Nesbit, 1964). The number of rats with lesions following either cadmium administration or ligation of superior epididymal vessels (but not small capital branches of the inferior epididymal vessels) approaches 30%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that the cadmium ion affects either the testicular vessels and their epididymal branches (Gunn, Gould, & Anderson, 1963), or their end-arterial capillary bed (Mason, Brown, Young & Nesbit, 1964). The number of rats with lesions following either cadmium administration or ligation of superior epididymal vessels (but not small capital branches of the inferior epididymal vessels) approaches 30%.…”
Section: Discussionmentioning
confidence: 99%
“…Although this region of the epididymis has the highest venous blood flow, it also has high metabolic activity (Setchell, Waites & Till, 1964). Blood flow through the epididymal branches which supply this region of the epididymis is presumed to be sluggish (Mason et al, 1964 (Kormano, 1968). Changes in the end-arterial capillary bed could be the site of U-5897 action.…”
Section: Discussionmentioning
confidence: 99%
“…selective destructive effect of cadmium on the testis of the rat and mouse have since been confirmed by Meek (1959), Kar & Das (1960), Gunn, Gould & Anderson (1961), Allanson & Deanesly (1962), Chiquoine (1964), Mason, Brown, Young & Nesbit (1964) and others. During studies on the induction of interstitial cell tumours of the testis by cadmium (Gunn, Gould & Anderson, 1963), we noted that cadmium failed to cause any degree of damage to the testis of the BALB/c mouse.…”
mentioning
confidence: 81%
“…These effects were also complimented with significantly reduced body weights. Mason et al (1964) describe effects of cadmiuminduced injury of the rat testis and also document the presence of vascular lesions, interstital edema, and hemorrhage. Colburn et al (1993) also identified literature documenting the potential for cadmium, lead, or mercury to act as estrogenic-rnimicing chemicals.…”
Section: Metalsmentioning
confidence: 99%